Terrains de jeu et stèles dans la région maya de Río Bec : rejet ou inutilité ? - Eric Taladoire (Journal de la Société des Américanistes)
The Río Bec region is renowned for its specific architectural style and its spatial organization in more or less equivalent groups of buildings. It is also characterized by its relative absence of inscribed monuments and ballcourts. In this contribution, we try to establish if this apparent scarcity reflects a real absence, and to interpret consequently the reasons of this phenomenon, as related to the regional sociopolitical organization.